CONCEPTUAL BOUNDARIES OF TEXT, DISCOURSE AND CONTEXT - Abduganiyeva Zebuniso (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
The terms text, discourse, and context are among the most widely used terms in linguistics. Despite the fact that these concepts are of central importance to discourse analysis, pragmatics, and text linguistics, they are frequently employed interchangeably or with overlapping meanings. The present article aims to undertake a systematic terminological clarification of all three concepts. The article argues that while the three terms are conceptually interdependent, they are analytically distinct. Establishing clear boundaries between these concepts is an essential condition for rigorous linguistic analysis and for the development of a coherent theoretical framework in text and discourse studies.